Personal learning environment: an experience with ESP teacher training. Issue 6 (17th August 2020) - Xu, Xiaoshu; Chan, Fai Man; Yilin, Sun
ABSTRACT: English for Specific Purposes (ESP) teacher development has become a crucial issue in ESP teaching and research. How to equip ESP teachers with necessary knowledge and skills in the digital era becomes a hot topic. A Personal Learning Environment (PLE) is a potential pedagogical approach to realize learning-centered in ESP teacher development. This paper is an exploratory research which attempts to integrate Learning Management System (LMS) with Personal Learning Environment for the training of ESP teachers at tertiary education in China. Based on the previous research on the seven-factor technology, pedagogy, and content knowledge (TPACK) framework and the five-factor skill Framework for ESP teachers in China, a PLE-ESP platform was built in the form of a website (www.esper.cn ). The platform was evaluated with 20 ESP participants within a two-month pilot study. A survey about the value and flexibility of the platform was carried out, the result of which indicated an improvement on the skills required in ESP teaching, learners' self-regulated learning competency and their ICT literacy. Recommendations were made for future research on the successful integration and maintenance of PLE and LMS.